Luteal Phase Support in Intrauterine Insemination Cycles: A Randomized Clinical Trial of Vaginal Versus Intramuscular Progesterone Administration - A Azargoon; G Joorabloo; M Mirmohammadkhani (JRI, 2022)
Background: Different progesterone doses and routes are used for luteal phase support in stimulated intrauterine insemination (IUI) cycles, but the optimal supplementation scheme has not yet been determined. Therefore, our aim was to compare the administration of two different doses of vaginal progesterone with two doses of intramuscular (IM) progesterone for luteal phase support in patients undergoing IUI cycles. Methods: In this randomized clinical trial, 312 women with unexplained or male-factor infertility intending to start IUI cycles between April 2015 and January 2018 were included. They were randomized into four groups (n=78/each) including group 1 who received IM progesterone in oil (25 mg daily), group 2 who received IM progesterone in oil (50 mg daily), group 3 who received progesterone suppository (400 mg daily), and group 4 who received progesterone suppository (800 mg daily; 400 mg twice daily). The primary outcome was the clinical pregnancy rate. The ongoing pregnancy rate, abortion rate, and patients’ satisfaction, and convenience the secondary outcomes. Results: In our study, the overall clinical and ongoing pregnancy rates per cycle with COS and IUI were 16.02% and 12.8%, respectively. There were no significant differences in clinical pregnancy, ongoing pregnancy, and abortion rates among groups (p=0.84). The overall patients’ satisfaction and convenience was significantly higher in the vaginal progesterone suppository groups than the IM progesterone groups (p=0.001). Conclusion: The results of this study showed that vaginal progesterone administration provides a more easy-to-use and convenient method than IM progesterone administration for luteal phase support in IUI cycles with comparable pregnancy rates.